Why Has Somaliland Not Been Recognised as A Sovereign State? - Issa-Salwe, Abdisalam M.; Osman, Abdullahi Salah (Advances in Social Sciences Research Journal, 2023)
After the collapse of the Somali state, civil war followed, leading people to turn to their ancestral homeland. Consequently, rudimental local administrations were formed with a provision of becoming part of a decentralised governance system in Somalia. However, one region stood differently by declaring itself a separate state, Somaliland, within the boundaries of the former British Somaliland Protectorate. To overcome the objections of African countries about the session, Somaliland claimed that its declaration of independence in 1991 was supposed to be a dissolution of the union rather than a declaration of separation. This idea follows in the footsteps of other failed federations, such as the United Arab Republic, which included Egypt and Syria from 1958 to 1961, or the Senegambia Confederation, which existed between Senegal and the Gambia from 1981 to 1989. These failed political unions symbolized the breakup of that union and the restoration of the protectorate's original, pre-1960 borders. (Gordon, 2023) Britain granted Somaliland independence on June 26 1960, and after four days, it joined with the former UN Italian Somaliland Trusteeship Territory to form the Republic of Somalia. Thus, Somaliland's case differed markedly from the other regions as it wanted to stand as a separate nation-state within Africa. Yet, over thirty years have passed, and Somaliland has not been recognised as a sovereign entity. To answer why it happened, we have to look at the historical factors on state formation in Africa and how newly independent countries treated colonially inherited boundaries.